Post COVID-19 Cognitive disorders: Virtual Reality and Augmented Reality as mental healthcare tools - Alvarado, Yoselie (2021)
Some time ago Virtual Reality and Augmented Reality were exclusively devoted to the gaming industry. Nowadays, both technologies are experiencing a deep interest from various spheres, including healthcare sector. The new infectious disease COVID-19 has had a catastrophic effect on the world’s demographics. Many patients with mild or severe COVID- 19 do not recover completely and present with a wide variety of chronic symptoms after infection, often of a neurological, cognitive or psychiatric nature. The most common signs of cognitive disorder can be summarized as mental fog, memory problems and concentration problems. The aim of this study was to analyze the opportunities for Virtual and Augmented Reality in the cognitive interventions related to mentioned disorders by searching for articles in scientific databases. We conclude that as these technologies and devices become cheaper and accessible worldwide, can at least be regarded as a rehabilitation therapy as effective as traditional training, and to some extent better than it.